Find the Area!

Calculus Level 5

If S = ( a , b ) R R : x = a , y = b , 2 x y 3 x 2 y = constant d y d x > 0 S = (a,b) \in R*R : x=a , y=b , 2xy - 3x^2y = \text{constant} \Rightarrow \frac{dy}{dx} > 0

S = ( x , y ) A B : 1 A 1 and 1 B 1 S' = (x,y) \in A*B : -1 \leq A\leq 1 \text{ and } -1 \leq B \leq 1

Then, Find the area of S S S \cap S'


The answer is 2.000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Oct 31, 2017

The set S S' is just a square of side length 2 that's centered at the origin of the x y xy- plane and has vertices at ( 1 , ± 1 ) ; ( 1 , ± 1 ) (-1, \pm 1); (1, \pm 1) .

Taking the derivative of the governing nonlinear equation for the set S S produces:

d d x ( 2 x y 3 x 2 y = C ) ( 2 y + 2 x y ) ( 6 x y + 3 x 2 y ) = 0 y = 2 y ( 3 x 1 ) x ( 2 3 x ) ; \frac{d}{dx} (2xy - 3x^{2}y = C) \Rightarrow (2y + 2xy') - (6xy + 3x^{2}y') = 0 \Rightarrow y' = \frac{2y(3x-1)}{x(2-3x)};

which we require x 0 , 1 3 , 2 3 x \ne 0, \frac{1}{3}, \frac{2}{3} AND y 0 y \ne 0 in order to satisfy y > 0. y' > 0. Upon examination of S S S \cap S' , its total area is just the set of all points ( x , y ) (x,y) contained within:

S 1 = ( x , y ) : x [ 1 , 0 ) ; y ( 0 , 1 ] S_1 = (x,y): x \in [-1,0); y \in (0,1] \Rightarrow AREA = ( 1 ) ( 1 ) = 1 (1)(1) = 1

S 2 = ( x , y ) : x ( 0 , 1 3 ) ; y [ 1 , 0 ) S_2 = (x,y): x \in (0, \frac{1}{3}); y \in [-1,0) \Rightarrow AREA = ( 1 3 ) ( 1 ) = 1 3 (\frac{1}{3})(1) = \frac{1}{3}

S 3 = ( x , y ) : x ( 1 3 , 2 3 ) ; y ( 0 , 1 ] S_3 = (x,y): x \in (\frac{1}{3}, \frac{2}{3}); y \in (0,1] \Rightarrow AREA = ( 1 3 ) ( 1 ) = 1 3 (\frac{1}{3})(1) = \frac{1}{3}

S 4 = ( x , y ) : x ( 2 3 , 1 ] ; y [ 1 , 0 ) S_4 = (x,y): x \in (\frac{2}{3}, 1]; y \in [-1,0) \Rightarrow AREA = ( 1 3 ) ( 1 ) = 1 3 (\frac{1}{3})(1) = \frac{1}{3}

or S 1 + S 2 + S 3 + S 4 = 1 + 3 ( 1 3 ) = 2 . S_1 + S_2 + S_3 + S_4 = 1 + 3(\frac{1}{3}) = \boxed{2}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...